Educational Action Research and Triple Helix principles in entrepreneurship education: introducing the EARTH design to explore individuals in Triple Helix collaboration - Michael Mandrup; Tine Lynfort Jensen (Triple Helix, 2017)
This article presents a practical approach on how to develop and explore an educational design combining Triple Helix theory and Educational Action Research for support of student learning and innovation activities in interaction with various actors. The design, termed EARTH, organizes systemic interactions between selected sectoral actors at the level of individuals in a context of innovative learning. Educational Action Research and Triple Helix theory share common principles seeking to generate change through collaboration, co-creation, equality, voluntarism, communication, and consensus-making between various actors. This creates a productive framework for supporting students' innovation activities and learning experiences, educational research, and organizational development. The EARTH design provides a basis for open innovation projects between students, teachers, researchers, and external partners from different sectors. Research data indicate that Triple Helix dynamics of substitution support students' competence and project developments. The design generates real-world innovation and entrepreneurship experiences for the students through mastery, social change, and vicarious learning. Furthermore, student teams organize self-initiated project interactions with diverse sectoral actors. The principles of Educational Action Research and Triple Helix are ideals that may be difficult to align due to asymmetries between involved partners unless such structural deficiencies are mutually addressed. This may be corrected by reorganizing the relations between Triple Helix spaces of knowledge, innovation, and consensus. The article concludes with a discussion of combining Educational Action Research with Triple Helix theory and some general perspectives for future developments of the EARTH design.
Keywords: 330; Educational Action Research; Innovation and Entrepreneurship Education; Students; Triple Helix